Inhibitory effect of 1,4,5,6-tetrahydroxy-7,8-diprenylxanthone against NSCLC with L858R/T790M/C797S mutant EGFR - Jing Wang; Yuna Wang; Shuanggou Zhang; Yana Qu; Ruohan Zhang; Xuanjun Wang; Jun Sheng; Peiyuan Sun (Scientific Reports)
Abstract Epidermal growth factor receptor (EGFR)-activating mutations are critical factors in the development of EGFR-driven non-small-cell lung cancer (NSCLC), and molecular targeted therapies have focused on inhibiting these mutations. EGFR tyrosine kinase inhibitors (TKIs) have remarkable inhibitory effects on NSCLC with EGFR mutations. However, acquired resistance limits the clinical application of EGFR-TKIs, highlighting the need for discovery of novel therapeutic strategies. 1,4,5,6-tetrahydroxy-7,8-diprenylxanthone is a natural product derived from Garcinia xanthochymus, has shown potential anti-tumor activity, but the underlying mechanism needs further elucidation. In this study, we developed Ba/F3 and NIH/3T3 cells harboring EGFR L858R/T790M/C797S mutation, and then found that 1,4,5,6-tetrahydroxy-7,8-diprenylxanthone exerted inhibitory effects against cells with EGFR L858R/T790M/C797S mutation. Additionally, 1,4,5,6-tetrahydroxy-7,8-diprenylxanthone exhibited potent anti-tumor activity against cells harboring the triple-mutant EGFR by promoting apoptosis and inducing changes in cell cycle distribution. Furthermore, 1,4,5,6-tetrahydroxy-7,8-diprenylxanthone was found to significantly reduce tumor growth via suppressing the phosphorylation of EGFR in tumor tissues. These effects are associated with binding of 1,4,5,6-tetrahydroxy-7,8-diprenylxanthone to EGFR resulting in the suppression of extracellular signal-regulated kinase (Erk) phosphorylation. In conclusion, our results suggest that 1,4,5,6-tetrahydroxy-7,8-diprenylxanthone may be a potential novel candidate for further investigation and treatment of NSCLC with the triple-mutant EGFR.